2021
DOI: 10.3390/jcm10153447
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter versus Isolated Surgical Aortic Valve Replacement in Young High-Risk Patients: A Propensity Score-Matched Analysis

Abstract: Background: Younger patients with severe symptomatic aortic stenosis are a particularly challenging collective with regard to the choice of intervention. High-risk patients younger than 75 years of age are often eligible for both the transcatheter aortic valve replacement (TAVR) and the isolated surgical aortic valve replacement (iSAVR). Data on the outcomes of both interventions in this set of patients are scarce. Methods: One hundred and forty-four propensity score-matched patients aged 75 years or less who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…There have been some propensity-matched studies that shed light on this topic. For instance, a study involving 72 pairs of high-risk patients, although utilizing mixed generations of TAVR valves, showed a lower in-hospital mortality rate but a higher risk of all-cause death at 5-year follow-up in the TAVR group [30]. Another propensity-matched analysis of 783 pairs of intermediate-risk patients (mean age: 81.7 years, mean STS score: 5.5) using newer-generation SAPIEN 3 valves demonstrated a comparable risk of death or disabling stroke at 5 years compared to SAVR [31].…”
Section: Discussionmentioning
confidence: 99%
“…There have been some propensity-matched studies that shed light on this topic. For instance, a study involving 72 pairs of high-risk patients, although utilizing mixed generations of TAVR valves, showed a lower in-hospital mortality rate but a higher risk of all-cause death at 5-year follow-up in the TAVR group [30]. Another propensity-matched analysis of 783 pairs of intermediate-risk patients (mean age: 81.7 years, mean STS score: 5.5) using newer-generation SAPIEN 3 valves demonstrated a comparable risk of death or disabling stroke at 5 years compared to SAVR [31].…”
Section: Discussionmentioning
confidence: 99%
“…A study done in 2021 by Virgili et al 4 showed that SAVR is the go‐to for the younger population because they are typically better surgical candidates. In addition, a study by Mach et al 16 showed that although short‐term survival (30 days postoperative) is higher in younger patients undergoing TAVR, SAVR was associated with better long‐term survival. TAVR would be ideal for all ages given its less invasive nature and lower complication rate.…”
Section: Discussionmentioning
confidence: 99%
“…Mach, M et al (2021) 10 showed Although the survival analysis revealed a higher in-hospital and 30-day survival rate for high-risk patients aged ≤75 years who underwent TAVR, iSAVR was associated with a significantly higher long-term survival rate.…”
Section: Austriamentioning
confidence: 99%